The Relationship of Organizational Citizenship Behavior with Job Satisfaction and Organizational Commitment of Nurses among Public Hospitals of Tehran University of Medical Sciences - Hossein Dargahi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2017)
Background: Organizational citizenship behavior is an essential tool for success of all organizations, since it is related variables of job satisfaction and organizational commitment. The organizations providing healthcare needs to develop their human resource especially nurses in order to promote organizational citizenship behaviors. Therefore, this study was aimed to determine the relationship of nurses’ organizational citizenship behavior with their job satisfaction and organizational commitment in public hospitals of Tehran University of Medical Sciences. Methods: This cross-sectional study was conducted on 375 nurses of 5 public hospitals. The sampling was proportional to the number of nurses who were randomly selected in each hospital. The research tools were 3 questionnaires including organizational citizenship behavior, nurses’ job satisfaction and organizational commitment. Data was analyzed using SPSS 20 software and t-test, ANOVA, Pearson coefficient were utilized to provide analytical results. Results: There was a positive and significant correlation between organizational citizenship behavior with job satisfaction, and with organizational commitment among nurses (p = 0.01). Moreover, there was a positive and significant relationship between job satisfaction and organizational commitment (p = 0.01). Conclusion: Considering the undesirable aspects of the research among nurses of Tehran University of Medical Sciences hospitals, It is recommended to improve the quality of work life, preventing burnout and creating an appropriate organizational atmosphere for nurses in the workplace. However, organizational justice, and other organizational variables should be assessed for improving of organizational citizenship behavior.